Bandwidth Saving Approach For De-duplication - Jaiswal, Roshni; Kumar, Nagendra (International Journal of Computer Sciences and Engineering, 2025)
The critical challenge of cloud storage or cloud computing is the organization of the continuously growing volume of data. Data de-duplication fundamentally submits to the exclusion of redundant data. However, indexing of all data is quiet maintained should that data ever be required. In general the data de-duplication eradicates the duplicate copies of duplicate data. Data De-duplication mechanism attain popularity from the academics and industrial as well, because the storage utilization in cloud storage is more efficient to store the data with the help of the cloud service providers. In this method redundant data is replaced with a pointer to the unique data copy. This reduces the hardware used to store data and the bandwidth costs required for transmitting and receiving purposes. This paper represents study of de-duplication as well as proposes a method for saving bandwidth and storage.